From Chalkboards to Smartboards: A Narrative Inquiry into the Experiences of Veteran Teachers Adapting to ICT (Shaheed Smriti Journal, 2025)
The rapid integration of information and communication technology (ICT) into education has significantly transformed teaching practices, often challenging veteran teachers trained in pre-digital pedagogies. This narrative inquiry examined the lived experiences of older teachers as they adapted to digital tools in classroom instruction. The study aimed to explore teachers’ anxieties, coping strategies, moments of achievement, and perceptions of self-efficacy during this transition. Data were collected through in-depth narrative interviews with veteran teachers working in secondary-level institutions. Using narrative analysis, the study identified patterns across participants’ stories while preserving individual voices. Findings revealed initial resistance and technological anxiety, followed by gradual adaptation facilitated by peer support, institutional pressure, and experiential learning. Teachers reportedincreased confidence over time, though concerns about workload and identity persisted. The study concluded that veteran teachers’ adaptation to ICT was not merely technical but deeply emotional and identity-driven. Understanding these experiences is essential for designing supportive professional development and inclusive digital education policies.